Defining chromosomal translocation risks in cancer - Hogenbirk, Marc A; Heideman, Marinus R; de Rink, Iris; Velds, Arno; Kerkhoven, Ron M; Wessels, Lodewyk F A; Jacobs, Heinz (Proceedings of the National Academy of Sciences - PNAS, 2016)
Chromosomal translocations are a hallmark of cancer. Unraveling the molecular mechanism of these rare genetic events requires a clear distinction between correlative and causative risk-determinants, where technical and analytical issues can be excluded. To meet this goal, we performed in-depth analyses of publicly available genome-wide datasets. In contrast to several recent reports, we demonstrate that chromosomal translocation risk is causally unrelated to promoter stalling (Spt5), transcriptional activity, or off-targeting activity of the activation-induced cytidine deaminase. Rather, an open chromatin configuration, which is not promoter-specific, explained the elevated translocation risk of promoter regions. Furthermore, the fact that gene size directly correlates with the translocation risk in mice and human cancers further demonstrated the general irrelevance of promoter-specific activities. Interestingly, a subset of translocations observed in cancer patients likely initiates from double-strand breaks induced by an access-independent process. Together, these unexpected and novel insights are fundamental in understanding the origin of chromosome translocations and, consequently, cancer.